Factors Determining The Delay in Access to Appropriate Emergency Obstetric Care During The Lockdown Period of The COVID-19 Pandemic: An Observational Study at A Tertiary Referral Centre - Triveni GS; Noopur Chawla; Aishwarya Kapur; Prateeksha BS; Kavita Badal; Manju puri (Journal of Epidemiology and Public Health, 2024)
Background: The WHO declared the COVID-19 pandemic as a public health emergency of inter-national concern following which many governments around the world adopted the most radical social distancing procedure, referred to as “lockdown”, to prevent the spread of the virus. As a result, unsupervised pregnancies and the absence of routine antenatal visits lead to dreaded maternal and fetal complications. This study determines the barriers to accessing emergency care by pregnant women during the lockdown period.Subjects and Method: This prospective study was conducted during the lockdown period in Delhi from 1 May 2021 to 31 May 2021. A total of 666 pregnant and postpartum patients admitted from casualty during this period were included. The variable of the study was various factors causing delays of more than 4 hours in accessing emergency care services by these patients after the onset of symptoms was assessed. This study used the conceptual model of Three Delays. The data was collected as per predesigned proforma. The demography, Obstetric profile, and various levels of delays were noted. The data was analyzed by frequencies and percentages using SPSS version 21.Results: Among 666 enrolled participants, about 55.7% were multigravida and 48.04% belonged to the upper-lower class. Nearly 43% of patients were illiterate. Antenatal delay of > 4 hours was observed in 590 patients (88.6%). In Level 1 delay, the main reasons for the delay were unawareness of danger signs (45.8%) and lockdown (30.93%). The major reason for the Level 2 delay was care declined at the previous center (33.93%). Reasons for the Level 3 delay were due to either unavailability of beds or overcrowding after reaching the facility.Conclusion: The unawareness of danger signs was the most common cause of delay. Hence, effective communication and counseling during the antenatal period have to be improved upon.